Negative Modulation of Macroautophagy by Stabilized HERPUD1 is Counteracted by an Increased ER-Lysosomal Network With Impact in Drug-Induced Stress Cell Survival - Vargas, Gabriela; Cortés, Omar; Arias-Muñoz, Eloisa; Hernández, Sergio; Cerda-Troncoso, Cristobal; Hernández, Laura; González, Alexis E.; Tatham, Michael H.; Bustamante, Hianara A.; Retamal, Claudio; Cancino, Jorge; Varas-Godoy, Manuel; et al. (Frontiers in Cell and Developmental Biology, 2022)
Macroautophagy and the ubiquitin proteasome system work as an interconnected network in the maintenance of cellular homeostasis. Indeed, efficient activation of macroautophagy upon nutritional deprivation is sustained by degradation of preexisting proteins by the proteasome. However, the specific substrates that are degraded by the proteasome in order to activate macroautophagy are currently unknown. By quantitative proteomic analysis we identified several proteins downregulated in response to starvation independently of ATG5 expression. Among them, the most significant was HERPUD1, an ER membrane protein with low expression and known to be degraded by the proteasome under normal conditions. Contrary, under ER stress, levels of HERPUD1 increased rapidly due to a blockage in its proteasomal degradation. Thus, we explored whether HERPUD1 stability could work as a negative regulator of autophagy. In this work, we expressed a version of HERPUD1 with its ubiquitin-like domain (UBL) deleted, which is known to be crucial for its proteasome degradation. In comparison to HERPUD1-WT, we found the UBL-deleted version caused a negative role on basal and induced macroautophagy. Unexpectedly, we found stabilized HERPUD1 promotes ER remodeling independent of unfolded protein response activation observing an increase in stacked-tubular structures resembling previously described tubular ER rearrangements. Importantly, a phosphomimetic S59D mutation within the UBL mimics the phenotype observed with the UBL-deleted version including an increase in HERPUD1 stability and ER remodeling together with a negative role on autophagy. Moreover, we found UBL-deleted version and HERPUD1-S59D trigger an increase in cellular size, whereas HERPUD1-S59D also causes an increased in nuclear size. Interestingly, ER remodeling by the deletion of the UBL and the phosphomimetic S59D version led to an increase in the number and function of lysosomes. In addition, the UBL-deleted version and phosphomimetic S59D version established a tight ER-lysosomal network with the presence of extended patches of ER-lysosomal membrane-contact sites condition that reveals an increase of cell survival under stress conditions. Altogether, we propose stabilized HERPUD1 downregulates macroautophagy favoring instead a closed interplay between the ER and lysosomes with consequences in drug-cell stress survival.